Green Pesantren Leadership: Shaping a Moderate Society for Environmental Conservation - Sudarsono, Sudarsono; Muadin, Akhmad; Tamam, Badrut (Institut Agama Islam Negeri Lhokseumawe, 2024)
This research aims to analyze the implementation of the concept of green pesantren conducted at Nurul Jadid Islamic Boarding School in Buleleng, Bali. The study depicts the participation of the Hindu community around the pesantren in the green pesantren program at Nurul Jadid Islamic Boarding School in Buleleng, Bali. It covers how the pesantren strives to build relationships with the Hindu community around it and how the Hindu community participates in the green pesantren program. The research method used is qualitative phenomenological research, which aims to explore and understand meanings. Data were collected through interviews, observations, and documentation processes. The research findings also undermine the stigma that pesantren are radical by showing their moderation. This relational aspect is based on the natural relationship between the pesantren and Hindu communities around it, which was initiated by its founder from its inception. Another aspect of this relationship is demonstrated by consultative functions of management in addressing various societal issues regardless of religious background. The active participation of the Hindu community around the pesantren in the green pesantren program stems from shared universal values regarding environmental preservation. The close relationship between the pesantren and surrounding Hindu communities is influenced by historical factors that are continuously socialized. Additionally, there are activities within this context that hold universal values.